Pengaruh Metode Image Streaming Terhadap Kemampuan Menulis Cerpen Siswa Kelas IX SMP Negeri 13 Makassar - Aprilianti, Aprilianti; Sakaria, Sakaria; Azis, Abdul (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the effect of the application of image streaming method on the ability to write short stories of students in class IX SMP Negeri 13 Makassar. The type of research used in this study is pre-experiment. In this study, a pre experimental design model of one group pretest and postest design was used. The research sample was class IX A students totalling 30 students. The instrument used in this study was a short story writing ability test. The data collection techniques used by researchers were observation and short story writing tests on pretest and posttest. The research data analysis used descriptive statistics and inferential statistics which were analysed with the help of the SPSS version 29 application. The results showed that there was a significant effect in the use of image streaming method on the ability to write short stories of class IX students of SMP Negeri 13 Makassar. This is because the use of image streaming method is able to foster students' interest and creativity in writing short stories. The ability to write short stories of students before and after applying the image streaming method has increased significantly, namely the average student score before using the field trip method is 58.46 and after using the field trip method is 79.1.